Storage Temperature or Thermal Treatments During Long Egg Storage Duration Influences Hatching Performance and Chick Quality - Guinebretière, Maryse; Puterflam, Julie; Keïta, Alassane; Réhault-Godbert, Sophie; Thomas, Rodolphe; Chartrin, Pascal; Cailleau-Audouin, Estelle; Coudert, Edouard; Collin, Anne (Frontiers in Physiology, 2022)
This study was designed to improve the hatching performance, chick robustness and poultry health in the event of long-term egg storage and suboptimal age of the reproductive flock. A total of 9,600 eggs from one young breeder flock (28 weeks of age, batch B) and 9,600 eggs from an older breeder flock (59 weeks of age, batch E) were used (ROSS 308). Each batch was separated into three sub-groups and stored for 14 days. The first sub-group of eggs (Cool, group C) was stored at 11.6°C. The second sub-group of eggs (Warm, group W) was stored at 18.3°C with two pre-incubation on days 6 and 10 of the storage period. The final sub-group of eggs (Control, group Ct) was stored at 18.3°C throughout the storage period. Eggs were similarly incubated and hatched birds were raised on the same experimental farm. In both batches, embryonic development was significantly more advanced in W eggs than in C and Ct eggs ( p < 0.01). In both batches, C and W treatments decreased early embryonic mortality by more than 10% compared with Ct, decreased the proportion of late-hatched chicks and improved the percentage of first grade chicks: in batch E, 42% of Ct eggs were first grade chicks vs. 57% in group W and 59% in group C. Benefits were even higher in batch B, where only 60% of Ct eggs gave first grade chicks vs. 83% in others groups. The hatching rate was thus higher in groups C and W regardless of flock age: for batch B eggs, 85% hatched in W and 84% in C vs. 62% in Ct, while for batch E eggs, 59% hatched in W and 61% in C vs. 45% in Ct. Day-old Ct chicks from batch E were heavier than W and C ones, and heavier than W chicks from batch B ( p < 0.05). Long-term parameters on farm were not significantly different between groups. Thermal treatments during the storage of eggs from both young and old breeder flocks counterbalance the negative effects of prolonged egg storage on hatching rate, without altering chicken performance during rearing.